INTERVENSI PELATIHAN PENILAIAN KINERJA PADA ATASAN UNTUK MENINGKATKAN PERCEIVED ORGANIZATIONAL SUPPORT & EMPLOYEE ENGAGEMENT - Holy Greata (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2017)
This study aims to look at the effectiveness of performance appraisal training programs to improve perceived organizational support and employee engagement among employees at YPTK educational institutions. This research uses a quantitative approach, with the before-and-after study design research design. The strength of this program is the ability to measure the impact of an intervention. Measuring devices perceived organizational support is an adaptation of the survey of perceived organizational support, while measuring instruments employee engagement is an adaptation of the Utrecht work engagement scale. The results of this study indicate the influence of perceived organizational support on employee engagement of 0.168 (p = 0.016 significant at l.o.s 0.05). Paired sample t-test results showed significant differences in perceived organizational support and employee engagement scores before and after the training and outreach of performance appraisal. Keywords: Perceived Organizational Suppor; Employee Engagement, Performance assessment Penelitian ini bertujuan melihat efektifitas program pelatihan penilaian kinerja untuk meningkatkan perceived organizational support dan employee engagement pada karyawan di lembaga pendidikan YPTK. Penelitian ini menggunakan pendekatan kuantitatif, dengan design penelitian the before-and-after study design. Kelebihan dari program ini adalah kemampuan untuk mengukur dampak dari sebuah intervensi. Alat ukur perceived organizational support merupakan adaptasi dari survey of perceived organizational support, sedangkan alat ukur employee engagement merupakan adaptasi dari Utrecht work engagement scale. Hasil penelitian ini menunjukkan adanya pengaruh perceived organizational support terhadap employee engagement sebesar 0.168 (p=0.016 signifikan pada l.o.s 0.05). Hasil uji paired sample t-test menunjukkan adanya perbedaan skor perceived organizational support dan employee engagement yang signifikan sebelum dan sesudah dilakukan pelatihan dan sosialisasi penilaian kinerja. Kata Kunci: Perceived Organizational Suppor; Employee Engagement, Penilaian Kinerja.